Performance of ``Penyuluh KB'' After the Transfer of Employment Status in East Java, Indonesia - Imron, Ali; Ilyas Marzuqi, Muhammad; Galih Setyawan, Katon (KnE Social Sciences, 2024)
Based on Law Number 23 of 2014 concerning Regional Government, the Penyuluh Keluarga Berencana (PKB) switched status to become a central employee. Previous studies have shown that when they were still regional employees, PKB’s performance had not run optimally. This study aims to describe the performance and operational mechanisms of family planning extension workers after the transfer of employment status. This study used a mixed-method approach by taking locations in Trenggalek, Ponorogo, and Tuban. The research variables include the characteristics of the family planning instructor, the characteristics of operational policies, operational mechanisms, and the performance of the PKB. The population is family planning extension workers who have experienced a change in employment status as central employees and the sample was selected purposively. Data were obtained through interviews and analyzed descriptively. The operational mechanism for family planning counselors must have legal support. The work plan made by PKB does not fully accommodate the needs of the community. The work targets assigned to PKB could not be achieved because they were too high, the quality of PKB was low, the age factor, and PKB’s administrative busyness. The lack of PKB performance shows that PKB’s performance is not optimal even though it has received performance allowances. Since the change in employment status, the cooperation between family planning counselors and midwives has changed in certain areas, resulting in reduced achievement of family planning programs. Therefore, capacity building and technical assistance are needed for PKB to spur the achievement of PPM performance targets optimally. Keywords: performance, “penyuluh KB”, status transfer, staffing